A fluorescent biosensor for cardiac biomarker myoglobin detection based on carbon dots and deoxyribonuclease I-aided target recycling signal amplification. Issue 8 (4th February 2019) - Chen, Jishun; Ran, Fengying; Chen, Qinhua; Luo, Dan; Ma, Weidong; Han, Tuo; Wang, Ceming; Wang, Congxia
Abstract : A sensitive biosensor has been developed to detect myoglobin (MB), which is an important cardiac biomarker and plays a major role in the diagnosis of acute myocardial infarction (AMI). Abstract : A sensitive biosensor using carbon dots and deoxyribonuclease I-aided target recycling signal amplification has been developed to detect myoglobin (MB), which is an important cardiac biomarker and plays a major role in the diagnosis of acute myocardial infarction (AMI). Here, in the absence of MB, the MB aptamer (Ap) is absorbed on the surface of carbon dots (CDs) through π–π stacking interactions, resulting in quenching of the fluorescent label by forming CD–aptamer complexes. Upon adding MB, the Ap sequences could be specifically recognized by MB, leading to the recovery of quenched fluorescence. Thus, quantitative evaluation of MB concentration has been achieved in a broad range from 50 pg mL −1 to 100 ng mL −1, and the detection limit is as low as 20 pg mL −1 . This strategy is capable of specific and sensitive detection of MB in human serum, urine, and saliva and can be used for the diagnosis of AMI in the future.